2010
DOI: 10.1111/j.1365-2184.2010.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term proliferation and characterization of human spermatogonial stem cells obtained from obstructive and non‐obstructive azoospermia under exogenous feeder‐free culture conditions

Abstract: These finding may support the idea that in vitro propagation of SSCs could be a useful tool for infertility treatment and study of reproductive biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 36 publications
7
88
0
Order By: Relevance
“…To reduce the interference of somatic cells, the subculturing MGSCs are maintained in media supplemented with growth factors. Glial cell linederived neurotrophic factor (GDNF) has far been demonstrated to play vital roles in SSC self-renewal and long-term cultures of SSCs across species [2,9,16,17,19,21,[25][26][27]32]. However, we observed that GDNF showed little positive effects on porcine MGSC colony formation (data not shown), which is in line with the previous report by Kuijk et al [20].…”
Section: Discussionsupporting
confidence: 76%
“…To reduce the interference of somatic cells, the subculturing MGSCs are maintained in media supplemented with growth factors. Glial cell linederived neurotrophic factor (GDNF) has far been demonstrated to play vital roles in SSC self-renewal and long-term cultures of SSCs across species [2,9,16,17,19,21,[25][26][27]32]. However, we observed that GDNF showed little positive effects on porcine MGSC colony formation (data not shown), which is in line with the previous report by Kuijk et al [20].…”
Section: Discussionsupporting
confidence: 76%
“…Although mGSCs have been differentiated into spermatogenic cells when they were co-cultured in vitro with feeder layer cells, treated with RA or transplantated in vivo (Feng et al 2002;Kanatsu-Shinohara et al 2003), few reports have shown that murine SSCs are induced in vitro to form haploid male germ cells using RA. Sycp3 and TH2B, specific markers of haploid male germ cells (Lim et al 2010;Li et al 2011), are expressed by haploid male germ cells, as seen in our result. In addition, the result from cell analysis by indirect immunofluorescence demonstrated that haploid male germ cells largely expressed protamine 1 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…As for OA patient, all genes were expressed; SCP3, H2B and TP1, which represent advanced stages of spermatogenesis (meiotic spermatocytes and spermatid respectively). All the gene markers for meiotic spermatogenesis were proven by previous study [16]. Our study has shown positive result with the present of SSC colonies in OA patient with HESC and BFGF media for 49 days of culture.…”
Section: Gene Expression Analysissupporting
confidence: 74%